Enantioselective Determination of the Insecticide Indoxacarb in Cucumber and Tomato by Chiral Liquid Chromatography–Tandem Mass Spectrometry. Issue 6 (28th May 2013) - Wang, Huanqing; Dong, Fengshou; Li, Yuanbo; Chen, Xiu; Cheng, Youpu; Xiang, Wensheng; Zheng, Yongquan
ABSTRACT A convenient and precise chiral method was developed and validated for measuring indoxacarb enantiomers in cucumber and tomato using liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) with a reversed‐phase Chiralpak AD‐RH column. The target analytes were extracted by acetonitrile and then purified by solid phase extraction (SPE) using NH2/Carb combined‐cartridge. Parameters including the matrix effect, linearity, precision, accuracy, and stability were used. Then the proposed method was successfully applied to investigate the possible enantioselective degradation of rac‐indoxacarb in cucumber and tomato under open conditions. The results indicated that the degradation of indoxacarb enantiomers followed first‐order kinetics in cucumber and tomato. The half‐lives of (+)‐S‐indoxacarb in cucumber and tomato were 3.0 and 5.9 days, respectively; while the (–)‐R‐indoxacarb were 7.3 and 12.2 days, respectively. The data of the half‐lives showed that (+)‐S‐indoxacarb was preferentially degraded in cucumber and tomato. Moreover, indoxacarb degraded faster in cucumber than in tomato. Chirality 25:350–354:, 2013. © 2013 Wiley Periodicals, Inc.